Effects of Enterococcus faecalis CECT 7121 on Cryptosporidium parvum infection in mice - Del Coco, Valeria Fernanda (2016)
Cryptosporidium is an opportunistic protozoan parasite of humans and animals worldwide and causes diarrheal disease that is typically self-limiting in immunocompetent hosts but often life threatening to immunocompromised individuals. However, there is a lack of completely efficient therapy available. Probiotics have attracted the attention as potential antiparasite compounds against protozoa involved in intestinal infections. This study investigated the effects of administration of probiotic Enterococcus faecalis CECT 7121 on Cryptosporidium parvum infection in immunosuppressed mice. Effects on C. parvum infection at the intestinal mucosa were studied and scored at each portion of the gut. It was demonstrated that Ef CECT 7121 interfered with C. parvum infection when both probiotic and parasite were present in the same intestinal location suggesting that Ef CECT 7121 supplementation can alleviate the negative effects of C. parvum infection.